Trends and correlational analyses among measures of academic achievement at the St. Luke's College of Medicine - Atienza, Maria Isabel M.
Objective: Measures of academic achievement were analyzed to determine performance of medical students. Specifically, the results of the Comprehensive Examination were subjected to a correlation and trends analyses to determine its relationship with the General Weighted Average (GWA). Individual subjects in the examination were analyzed in relation to the corresponding Subject Weighted Averages to determine strengths and weaknesses in student performance. General curricular trends were then inferred. Setting: St. Luke's College of Medicine-William H. Quasha Memorial. Methodology: Data from 365 students who graduated from 2002 to 2005 were included in the analysis. The independent variable included the Comprehensive Examination results, while the dependent variables included the GWA, the Subject Weighted Averages, and internship grades. Data was analyzed using the Pearson and the Spearman tests, and a linear regression analysis. Results: Student's Comprehensive Examination grades showed high correlation with the GWA, with correlation coefficients that demonstrated improvement from 2002 to 2005. There were generally high correlations among subjects. Subject strengths were identified based on the subject weighted averages. Basic subjects noted to have high failure rates were Biochemistry, Anatomy, Physiology and Pharmacology. A notable poor performance was seen in batch 2005, with an increase in failure rates among several subjects. The subjects where students consistently showed higher grades included Ophthalmology-Otorhinolaryngology, Obstetrics-Gynecology, and Behavioral Science. Conclusions and Recommendations: The comprehensive Examination results exhibited a highly significant correlation with the corresponding Subject Weighted Averages. Recommendations for curricular review and improvements in assessment measures for academic achievement are presented.